Transthyretin proteoforms of intraocular origin in human subretinal fluid. (September 2022) - Chen, Jianzhong; Cao, Dongfeng; Fortmann, Seth D.; Curcio, Christine A.; Feist, Richard M.; Crosson, Jason N.
Abstract: Understanding the molecular composition of ocular tissues and fluids could inform new approaches to prevalent causes of blindness. Subretinal fluid accumulating between the photoreceptor outer segments and retinal pigment epithelium (RPE) is potentially a rich source of proteins and lipids normally cycling among outer retinal cells and choroid. Herein, intact post-translationally modified proteins (proteoforms) were extracted from subretinal fluids of five patients with rhegmatogenous retinal detachment (RRD), analyzed by tandem mass spectrometry, and compared to published data on these same proteins as synthesized by other organs. Single-nuclei transcriptomic data from non-diseased human retina/RPE were used to identify whether proteins in subretinal fluid were of potential ocular origin. Two human donor eyes with normal maculas were immunoprobed for transthyretin (TTR) with appropriate controls. The three most abundant proteins detected in subretinal fluid were albumin, TTR, and apolipoprotein A-I. Remarkably, TTR relative to the other proteins was more abundant than its serum counterpart, suggestive of TTR being synthesized predominantly locally. Six proteoforms of TTR were detected, with the relative amount of glutathionylated TTR being much higher in the subretinal fluid (12–43%) than values reported for serum (<5%) and cerebrospinal fluid (0.4–13%). Moreover, a putative glycosylated TTR dimer of 32, 428 Da was detected as the fourth most abundant protein. The high abundance of TTR and putative TTR dimer in subretinal fluid was supported by analysis of available single-nuclei transcriptomic data, which showed strong and specific signal for TTR in RPE. Immunohistochemistry further showed strong diffuse TTR immunoreactivity in choroidal stroma that contrasted with vertically aligned signal in the outer segment zone of the subretinal space and negligible signal in RPE cell bodies. These results suggest that TTR in the retina is synthesized intraocularly, and glutathionylation is crucial for its normal function. Further studies on the composition, function, and quantities of TTR and other proteoforms in subretinal fluid could inform mechanisms, diagnostic methods, and treatment strategies for age-related macular degeneration, familial amyloidosis, and other retinal diseases involving dysregulation of physiologic lipid transfer and oxidative stress. Highlights: Subretinal fluid removed during retinal detachment repair is rich in transthyretin. Transthyretin in subretinal fluid, unlike elsewhere, is highly glutathionylated. A putative glycosylated transthyretin dimer of 32, 428 Da is detected. Transthyretin is synthesized in the RPE and secreted into interphotoreceptor matrix.